Brazilian Curie isothermal mapping: the THERMOMAG model - Suze N. P. Guimaraes; Beatriz L. de Jesus; Fábio P. Vieira (Geothermal Energy)
Abstract Geothermally, the lithosphere can be defined as the outermost layer of the Earth in which heat is primarily transferred by conduction. It typically includes the crust and upper mantle. Crustal structural provinces are segments of the crust that have the same range of geochronologic ages and thermogeologic histories. The crustal geothermal regime on the continent is determined by many factors, including heat flow, vertical and lateral variations in thermal conductivity, radiogenic heat production, tectonic history, and surface thermal processes. Studying the thermal structure of the crust by geotectonically characterizing the upper lithospheric layer makes it possible to understand the internal heat flow as an energy source potential, which remains unknown due to limited exploration research. This study presents a crustal heat distribution model using direct temperature data and indirect estimates derived from crustal magnetic field information, the THERMOMAG model. The subsurface layers are identified in order to characterize the entire magnetized crust, thus delimiting the Curie surface (isothermal limit of 580 °C), which is directly linked to the exploration of crustal energy resources. Spectral analysis of the aeromagnetic data was used to estimate the depth of the layer related to the deepest crustal sources and their spatial distribution, thus comparing these discoveries with geothermal fields known from direct modeling. The cross-check in the values for the Curie isotherm inserted by the thermomagnetic model allowed a correction in the values obtained indirectly, called the thermomagnetic correction factor (β) which is directly correlated to the amount of data distributed in the different provinces. The results of this model suggest that the greatest Curie depths in Brazil (> 44 km) are located in the São Francisco and Parnaiba provinces, and for the others, the mean values are 23 km. The regions of geothermal anomalies are found essentially in the northwest region of Paraná province, the northern part of Tocantins West province, the south-central part of Tocantins East province, the north-central part of São Francisco province, and the northeast region of Borborema province. The Brazilian structural provinces have thermal conductivity values ranging from 2.1 to 2.7 W/mK.